Students' Creative Thinking Ability in Solving Open-Ended Problems - Munadiya Yunadia; R. Ruslan; R. Rusli; Hastuty Hastuty (PT ARRUS Intelektual Indonesia, 2023)
This study aims to describe the level of creative thinking ability in solving open-ended problems in class XII MAN Pangkep. This research is a qualitative descriptive research. The research subjects included all students of class XII MIA 5 MAN Pangkep in the 2021/2022 school year consisting of 33 students and 3 students representing each level became interview subjects. The selection of research subjects is based on the creative thinking ability test at each level of creative thinking ability. The data collection technique in this study was the administration of creative thinking ability tests and interviews. Analysis of creative thinking ability tests refers to three indicators of creative thinking ability, namely fluency, flexibility and novelty. The results of this study indicate that students of grade XII MAN Pangkep have three levels of creative thinking ability, namely (1) students with level 4 (very creative) fulfill all three aspects of creative thinking ability namely fluency, flexibility, and novelty which means students are able to solve open-ended problems with many answers, various ways/methods and show new solutions; (2) students with level 3 (creative) fulfill two aspects of creative thinking ability namely fluency and flexibility which means students are able to solve open-ended problems with many answers and various ways; and (3) students with level 1 (less creative) show aspects of fluency which means students are able to solve open-ended problems with many answers.